Punishment, prison, and Social Work: appreciating textual outputs - Forti, Valeria Lucília; Santos Ferreira, Beatriz; Medrado Abrantes, Marcia (Argumentum, 2020)
The text provokes critical reflection on the investment made by social workers in theoretical-practical links through textual output aimed specifically at the work of this professional in prisons. It refers to partial data from documentary research that evidences the lack of debates and analyzes related to work processes in this complex socio-occupational field, particularly considering the indispensability of such debates for training and continuous professional development. The most recent publications from ENPESS and CBAS are used, exposing the dissonance between the complexity of the field and the limited textual output of the professional. It also highlights the historical character of punishment and prison and the institutions that have traditionally relied on this professional.Keywords: Social Work. Work. Prison. Textual output. Professional ethics.